Effect of vermicompost application on MD2 pineapple productivity, soil properties and bioactivity under field conditions / Mawiyah Mahmud - Mawiyah , Mahmud (2018)
In the present study, a two-year field trial of pineapple, Ananas comosus var. MD2 plants (in vivo and ex vitro) was conducted based on a factorial randomized complete block design (RCBD) with three treatments in Jelebu, Malaysia from January 2015 until December 2016 to elucidate the effects of vermicompost (compared to supplementation with chemical fertilizer and no fertilizer) on the morphophysiology and yield performance of in vivo and ex vitro grown MD2 pineapple. The effect of vermicompost on sandy loam soil and plant nutrients of pineapple were also evaluated. Furthermore, studies were conducted to determine the effect of vermicompost on the bioactive compounds and antioxidant potential of the MD2 fruit extracts. In this study, vermicompost was applied onto the soil during transplanting, followed by a second application at seven MAP (months after planting) at the rate of 10 tan ha-1. On the other hand, the chemical fertilizer was applied based on the normal conventional cultivation practice. The morphology of the plants was evaluated every month, and the fruits that were produced were subjected to quality analysis (physical, physicochemical and sensory analysis). The soil and D-leaf samples at six MAP (S1) and during red bud stage (S2; 10 MAP, in vivo plant; 16 MAP, ex vitro plant) were used to determine the soil and plant nutrient contents. For determination of antioxidant potential, three different test systems were used (ABTS, DPPH and FRAP). Data analysis revealed that there was no significant difference between plants supplied with chemical fertilizer and vermicompost in terms of plant height or the length and width of D-leaves (P ≤0.05). However, based on SEM studies, pineapple plants supplemented with vermicompost showed higher stomatal density in the D-leaf. Moreover, different fertilization treatments were found to affect the yield and physical characteristics of the resulting fruits. In vivo plants supplied with chemical fertilizer produced the highest fruit yield (136.97 t ha−1) with the largest fruit size, followed by vermicompost (121.39 t ha−1) and the control (94.93 t ha−1). Similar trend was observed on ex vitro plants but smaller in size, contained higher total soluble solids (12.6 °Brix), titratable acidity (0.39 g kg-1), total solids (20.841% wt/wt) and ascorbic acid (44.577 μg AA/g FW fruit). Soil pH was increased after a second supplementation of vermicompost and contained significantly higher total N in the soils compared to the control. The results showed that the antioxidant potential was lower in the methanolic extract of fruits harvested from ex vitro plants than in vivo plants. Based on HPLC analysis, only β-carotene was detected in the freeze-dried fruit extracts of all treatments from in vivo plants. However, for ex vitro plants supplemented with chemical fertilizer, both α-carotene and β-carotene were detected. Also, based on the cost analysis conducted, it was shown that the total cost (fertilizer and labour) for plants grown with vermicompost was lower than plants grown with chemical fertilizer.